2014
DOI: 10.1039/c3sm53202j
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of ionic conductivity from structural dynamics in polymerized ionic liquids

Abstract: Charge transport and structural dynamics in low molecular weight and polymerized 1-vinyl-3-pentylimidazolium bis(trifluoromethylsulfonyl)imide ionic liquids (ILs) are investigated by a combination of broadband dielectric spectroscopy, dynamic mechanical spectroscopy and differential scanning calorimetry. While the dc conductivity and fluidity exhibit practically identical temperature dependence for the non-polymerized IL, a significant decoupling of ionic conduction from structural dynamics is observed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
187
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(205 citation statements)
references
References 27 publications
15
187
3
Order By: Relevance
“…33 PolyILs have two to three orders of magnitude lower ionic conductivity than IL monomers, while retaining high thermal and electrochemical stability. [116][117][118][119][120][121] PolyILs have significant advantage due to high cation transference number, since the anion is attached to the polymer chain. Starting at early 1990s Ohno et al published a series of investigations of vinyl imidazole based PolyILs, 116,117 in which they suggested that the flexibility of the charged site of the polymer controls the ion transport.…”
Section: 91mentioning
confidence: 99%
“…33 PolyILs have two to three orders of magnitude lower ionic conductivity than IL monomers, while retaining high thermal and electrochemical stability. [116][117][118][119][120][121] PolyILs have significant advantage due to high cation transference number, since the anion is attached to the polymer chain. Starting at early 1990s Ohno et al published a series of investigations of vinyl imidazole based PolyILs, 116,117 in which they suggested that the flexibility of the charged site of the polymer controls the ion transport.…”
Section: 91mentioning
confidence: 99%
“…This observation is consistent with that reported for chemically crosslinked ion-conducting networks generated from copolymerization of ionic liquid monomers with varying contents of multi-functional crosslinkers, 59 and polymer electrolytes based on PEO and LiNTf2. 51 Although the complexation of Ni 2+ by imidazole moieties couples ion transport to the polymer segmental dynamics, this does not translate into a single NTf2 -conductor, such as polymerized ionic liquids based on imidazolium, [33][34][35][36][37][38][39] as the kinetically labile nature of metal-ligand coordination bonds allows for bond breakage and formation on time scales that could facilitate long-range Ni 2+ transport as long as the operating temperature is above Tg. A more quantitative relationship between ion content and mobility is currently under investigation and outside the scope of this work.…”
Section: Linear Dielectric Responsementioning
confidence: 99%
“…In particular, polymers based on imidazole and histidine ligands are interesting due to a preexisting understanding of the reactivity 31 and interactions with transition metal ions in chemical and biological systems. 32 Investigations of these materials have primarily focused on quaternized imidazolium [33][34][35][36][37][38][39] and histammonium [40][41][42] ions (i.e., polymerized ionic liquids), yet imidazole and histidine moieties are capable of interacting with alkali, alkaline earth, and transition metal ions thus promoting salt dissociation and influencing the ion conducting and mechanical properties ( Figure 1). From a materials chemistry standpoint, these materials constitute macromolecular analogues of chelating ionic liquids, a set of concentrated electrolytes known to solubilize ions such as Zn 2+ due to metal-ligand coordination.…”
Section: Introductionmentioning
confidence: 99%
“…They have been presented as greener 15 alternatives to organic solvent mainly because of negligible vapor pressures and possible liquid-liquid extraction. 1 However, their use in devices such as medical, biosensors or energy storage is often limited by the liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency range used for impedance measurements was 184 kHz -20 mHz and the amplitude used was 7 mV. 15 …”
mentioning
confidence: 99%